2022
DOI: 10.3390/nu14030676
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Spirulina Consumption on Brain Health

Abstract: Spirulina is a microscopic, filamentous cyanobacterium that grows in alkaline water bodies. It is extensively utilized as a nutraceutical food supplement all over the world due to its high levels of functional compounds, such as phycocyanins, phenols and polysaccharides, with anti-inflammatory, antioxidant, immunomodulating properties both in vivo and in vitro. Several scientific publications have suggested its positive effects in various pathologies such as cardiovascular diseases, hypercholesterolemia, hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 158 publications
(173 reference statements)
2
21
0
5
Order By: Relevance
“…Endothelin-1 was found to be significantly lower in Spirulinal group GIII than in Spirulinal group GII, as shown in the same table. The study's findings are in agreement with my own findings (Trotta et al .,2022). These goods, including Spirulinal, are anti-oxidant/anti-inflammatory/antitumor, and they also improve immunity and protect organs from harm.…”
Section: Endothelin-1supporting
confidence: 91%
“…Endothelin-1 was found to be significantly lower in Spirulinal group GIII than in Spirulinal group GII, as shown in the same table. The study's findings are in agreement with my own findings (Trotta et al .,2022). These goods, including Spirulinal, are anti-oxidant/anti-inflammatory/antitumor, and they also improve immunity and protect organs from harm.…”
Section: Endothelin-1supporting
confidence: 91%
“…In addition, it can modulate the immune system and the bioactivity of macrophages by activating T and B cells, promoting the production of antibodies and cytokines, increasing the concentration of NK cells in tissues, and encouraging the generation of antibodies [ 84 ]. Spirulina is a rich source of antioxidants and anti-inflammatory substances, which are able to not only support and develop physiological functions of the nervous system and brain, as well as compensate for nutritional deficiencies, but also promote a beneficial immune response [ 5 ]. Several studies have also demonstrated the positive effects of spirulina, including the immunological and antioxidant effects that are attributable to its carbohydrate content, particularly polysaccharides.…”
Section: Potential Health Benefits Of Spirulina From a Human Nutritio...mentioning
confidence: 99%
“…In addition to bolstering the immune system, the presence of these compounds is associated with a reduced risk of developing neurodegenerative conditions, such as Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis, in particular. Spirulina is regarded as a natural medicine and is utilized in the manufacturing of functional foods and nutritional supplements all over the world due to the qualities that have been described [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Living in tropical and subtropical warm lakes with a high carbonate and bicarbonate content, and high pH and salinity 2 , Arthrospira is rich in proteins, minerals, vitamin B 12 , β-carotene, and essential fatty acids, such as γ-linolenic acid which can inhibit bacteria and virus, regulate the immune function, and can prevent diseases like hypertension, diabetes and tumor, etc. 3 . Thanks to its high protein content of up to approximately 60–70% on a dry weight, the amino acids present in Arthrospira match the proportions recommended by the Food and Agriculture Organization (FAO) 4 .…”
Section: Introductionmentioning
confidence: 99%